Hepatic Visceral Larva Migrans: A Case Series - Jain, Suchita; Jain, Ajay K.; Agrawal, Praveen; Bhagat, Priyanka; Chatterji, Debi (Journal of Gastrointestinal Infections, 2023)
Visceral larva migrans is an uncommon systemic parasitic infection of liver caused by second-stage larva of Toxocara canis or Toxocara catis. The liver is the most common visceral organ to be involved. The diagnosis is usually delayed because of a lack of awareness about visceral larva migrans in adults, with most patients confused with either an abscess or neoplastic nodules. Heterogenous solid cystic, multiple hypodense, and hypovascular lesions on imaging with peripheral eosinophilia make the diagnosis in most cases. We present four adult patients with 2 to 4 weeks of fever and very high peripheral eosinophilia. The liver biopsy in three cases revealed an eosinophilic abscess. All cases on treatment with albendazole showed a good response. Visceral larva migrans must be considered in patients with heterogenous, hypovascular space-occupying liver lesions presenting with fever and peripheral eosinophilia.
Keywords: visceral larva migrans; eosinophilia; parasitic infections of the liver; toxocariasis; albendazole; eosinophilic abscess